Laboratório na escola: possibilidades para o ensino de Matemática e formação docente - Renata Rodrigues de Matos Oliveira (2017)
This dissertation points my experiments of implantation of Laboratory of Mathematics Teaching (LEM) in two public schools in MG; From the experiences the questions were asked: What is the teacher's perception of the LEM space for the teaching processes in the public school? Is this also a space for teacher training? Thus, the purpose of this research is to present concepts of LEM for elementary school, with objectives and proposals that guide its applicability and functionality, as well as to allow the discussion of this space as a possibility for continuing education for teachers. Works in the area dealing with understanding about LEM were listed. We also held a meeting with teachers from different areas who work in the LEM and interviews with teachers of Mathematics. Our analysis intended to contemplate the conceptual and practical aspects, in order to present a didactic material, a site that helps the creation and use of LEM in schools, encouraging a better understanding of the area. The teachers emphasize the importance of collective or individual planning to work in the LEM and for this the working conditions need to be offered and guaranteed. We perceive the importance of LEM as an institutionalized space and, as such, recognized in the pedagogical project of the school. We analyze that the space represents possibilities of enrichment of the teaching practices of Mathematics and other areas, in that it invites to the investigation and sharing, which makes the students participate with joy and disposition And facilitates teaching for the teacher. With the planning and the own differentiated way of treating the mathematical contents, the teacher expands its formation.